1997
DOI: 10.1017/s002211209700493x
|View full text |Cite
|
Sign up to set email alerts
|

Energy transfer in rotating turbulence

Abstract: The influence of rotation on the spectral energy transfer of homogeneous turbulence is investigated in this paper. Given the fact that linear dynamics, e.g. the inertial waves regime found in an RDT (rapid distortion theory) analysis, cannot affect a homogeneous isotropic turbulent flow, the study of nonlinear dynamics is of prime importance in the case of rotating flows. Previous theoretical (including both weakly nonlinear and EDQNM theories), experimental and DNS (direct numerical simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
319
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(349 citation statements)
references
References 17 publications
22
319
1
Order By: Relevance
“…The realizability condition, or condition for the Hermitian covariance matrixR(k, t) to be definite-positive, can be written as (Cambon, Mansour & Godeferd 1997)…”
Section: The (E Z) Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The realizability condition, or condition for the Hermitian covariance matrixR(k, t) to be definite-positive, can be written as (Cambon, Mansour & Godeferd 1997)…”
Section: The (E Z) Decompositionmentioning
confidence: 99%
“…Here, λ, λ and λ are angles that characterize the rotation of the plane of the triad around k, p and q respectively; x, y and z refer to the cosines of the internal angles of the triangle formed by the triad. The above expressions for the transfer terms T (E ) (k, t) and T (Z) (k, t) are also derived in Cambon et al (1997) in a different way. Similarly, one can deduce a closed-form expression of the transfer term T (RTI) (k, t) defined by (2.18), which generates the 'slow' component of the pressure-strain rate tensor:…”
Section: (Iv)mentioning
confidence: 99%
“…The period of the oscillations is thus proportional to the Rossby number Ro= ͗uЈ͘ TA / ͑2⍀L͒, with L = D m so these slow dynamics are essentially governed by resonant triads. 23 Now consider the right panels in Fig. 11.…”
Section: A Characterization Of Parameter Tripletsˆ50 ω 4‰mentioning
confidence: 99%
“…Numerical simulations have shown that the faster growth of certain integral length scales is also related to the inhibited energy cascade. [21][22][23] Among the most recent experimental studies are those by Baroud et al, 13,14 Morize and co-workers, 15,24 and by Davidson an co-workers. 16, 17 Baroud and co-workers studied the flow in a rotating annulus with forcing created by pumping water into ͑out of͒ the annulus through an inner ͑outer͒ ring of holes on the bottom of the annulus.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments of decaying turbulence in rotating tanks show the growth of length scales aligned with the rotation axis, giving evidence that turbulence developing in rotating systems is highly anisotropic. Both linear [14,15] and nonlinear [16,17] mechanisms have been advocated to explain the observed growth. Numerical simulations of rotating flows have also indicated a general trend towards two-dimensionalization [8,17] and some studies [9] have reported a split of the energy cascade into a downscale and an upscale process.…”
Section: Introductionmentioning
confidence: 99%